2009
DOI: 10.1002/jcp.21721
|View full text |Cite
|
Sign up to set email alerts
|

5′‐N‐ethylcarboxamide induces IL‐6 expression via MAPKs and NF‐κB activation through Akt, Ca2+/PKC, cAMP signaling pathways in mouse embryonic stem cells

Abstract: Many studies suggest that adenosine modulates cell responses in a wide array of tissues through potent and selective regulation of cytokine production. This study examined the effects of adenosine on interleukin (IL)-6 expression and its related signal pathways in mouse embryonic stem (ES) cells. In this study, the adenosine analogue 5'-N-ethylcarboxamide (NECA) increased IL-6 protein expression level. Mouse ES cells expressed the A(1), A(2A), A(2B), and A(3) adenosine receptors (ARs), whose expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(8 reference statements)
3
6
0
Order By: Relevance
“…These data are in line with the study of Aloisi and colleagues, which demonstrated that LIF modulation by pro-inflammatory cytokines in human astrocytes was mediated through PKC activation [59]. Moreover, PKC has also been shown to be essential in IL-6 regulation [47,48,62,65], revealing a prominent role for PKC in the signaling pathway controlling LIF gene expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data are in line with the study of Aloisi and colleagues, which demonstrated that LIF modulation by pro-inflammatory cytokines in human astrocytes was mediated through PKC activation [59]. Moreover, PKC has also been shown to be essential in IL-6 regulation [47,48,62,65], revealing a prominent role for PKC in the signaling pathway controlling LIF gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we show here that adenosine-dependent LIF expression in astrocytes is regulated through the NF-κB transcription factor. This observation is in line with several studies showing an NF-κB-dependent regulation of IL-6 gene by this transcription factor in several cell types [38,50,51,65,66]. It has been shown that NECA-induced NF-κB activation and the resultant IL-6 gene expression was abolished by inhibitors of MAPK pathways [65].…”
Section: Discussionsupporting
confidence: 88%
“…It is noteworthy that Chiou et al reported a paracrine feedback regulatory loop between miR142-3p and IL-6 in GBM cells [33], in which IL-6 suppresses miR142-3p expression through increasing its promoter methylation, while miR142-3p inhibits IL-6 expression and secretion by directly targeting IL-6 3′UTR. Additionally, AKT is previously reported to play positive role in regulating IL-6 biogenesis and secretion by NF-kappaB and MAPK pathway, supporting that AKT may upstream modulator in IL-6 pro-inflammatory pathway [61, 62]. Although the definition of autocrine and paracrine differs from each other, our solid evidence demonstrates the paracrinal effect of DDP-treated GBM cells but the autocrinal effect is unable to be ruled out from our results.…”
Section: Discussionmentioning
confidence: 44%
“…Regarding the previous studies, the IL-6 regulatory circuit can be jointly categorized as autocrine/paracrine rather than an individual one [63–67]. Additionally, AKT is previously reported to play positive role in regulating IL-6 biogenesis and secretion by NF-kB and MAPK pathway, supporting the notion that AKT may upstream modulator in IL-6 pro-inflammatory pathway [61, 62]. Recently, IL-6 is reported to play a positive role in regulating AKT/PI3K activity to promote tumor cell survival [68].…”
Section: Discussionmentioning
confidence: 92%
“…These results indicate that Cx43 phosphorylation is dependent on AR-mediated signaling in mouse ES cells. Previously, we demonstrated that all AR subtype mRNAs can be detected in mouse ES cells (Kim et al, 2009). ARs might function as novel targets in physiology of mouse ES cells.…”
Section: Discussionmentioning
confidence: 96%